The influence of nectar production and floral visitors on the female reproductive success of Inga (Fabaceae): a field experiment - Cruz Netto, Oswaldo (2015)
Floral morphology, nectar secretion strategies and the contribution of pollinators to the reproductive success of plants provide important clues regarding the levels of generalization or specialization in pollination systems. Anthesis throughout the day and night allows flowers to be visited by diurnal and nocturnal pollinators, promoting generalization or specialization. We studied three species in the diverse tropical genus Inga to: (1) quantify the response of flowers to successive nectar extractions and (2) determine the contribution of diurnal and nocturnal floral visitors to female reproductive success. Inga flowers could be clearly distinguished mainly on the basis of the staminal tube diameter and the quantities of filaments and pollen grains. Successive nectar removals led to a decrease of 60% in the total nectar secretion in I. vera and to increases of 20% in I. ingoides and 10% in I. striata. Despite these differences, the studied Inga spp. exhibited similar patterns of visitation rates and shared diurnal and nocturnal pollinators. Nocturnal pollinators contributed ten times more than diurnal pollinators to the female reproductive success of Inga. Floral morphology, nectar secretion patterns and pollination ecology data suggest an evolutionary trend towards specialization for nocturnal pollinators in Inga spp. with crepuscular or nocturnal flowers.